Viagem a Marte: uma proposta ?STEM? para contribuir no ensino de astronomia na Educa??o B?sica - Santos Junior, Omar Ferreira dos (2024)
STEM (acronym for Science, Technology, Engineering and Mathematics) is a global trend that is highlighted in educational debates related to vocational and economic objectives. This movement aims to help the next generations develop new skills and abilities with the aim of promoting strategic technological development capable of solving current problems related to the areas of Science and Technology (S&T). This work, supported by exploratory and descriptive research, aimed to contribute to the training and development of Basic Education students in the face of the educational challenges of the 21st century and stimulate interest in S&T through Astronomy, considering the approach of STEM education and other models pedagogical. Following the four pillars of UNESCO education, the STEM Learning pedagogical model and the guidelines presented in the National Common Curricular Base (BNCC), the actions carried out during the research sought to encourage actions of intellectual curiosity in students to investigate and solve problems with special reference to the theme of space explorations on the planet Mars, in Astronomy, understanding the importance of investigating conditions and traces of life on other planets, using pedagogical tools related to STEM areas as an interdisciplinary component. The educational product generated by this work is a teacher's guide containing a series of guidelines for the development of organized and detailed theoretical-practical activities suitable for STEM education that can be addressed in workshops, work shows, scientific dissemination, extension course or elective course. As a result of the scientific dissemination actions carried out, the relevance of works like this for promoting engagement and interest in STEM was realized, that the chosen theme proved to be current and relevant, in addition to the need to prepare students and education professionals for the educational challenges of the 21st century.